2016
DOI: 10.1016/j.actao.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring austral and cyclonic swells in the “Iles Eparses” (Mozambique channel) from microseismic noise

Abstract: a b s t r a c tWe deployed five broadband three-components seismic stations in the Iles Eparses in the south-west Indian Ocean and on Mayotte Island, between April 2011 and January 2014. These small and remote oceanic islands suffer the effects of strong ocean swells that affect their coastal environments but most islands are not instrumented by wave gauges to characterize the swells. However, wave action on the coast causes high levels of ground vibrations in the solid earth, so-called microseismic noise. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The source of this noise is located in the southern Ocean, as demonstrated by Davy et al (2015) from the analysis of permanent seismic stations located in the Indian Ocean and also modelled from wave dynamics (Ardhuin et al 2011;. This particular swell event was recently analysed at the seismic stations located in the Mozambique channels (Barruol et al 2016) and the map of this swell propagation in the SW Indian Ocean was presented in their Fig. 3.…”
Section: Austral Swell-related Seismic Noise Recorded By a Seismologimentioning
confidence: 95%
See 2 more Smart Citations
“…The source of this noise is located in the southern Ocean, as demonstrated by Davy et al (2015) from the analysis of permanent seismic stations located in the Indian Ocean and also modelled from wave dynamics (Ardhuin et al 2011;. This particular swell event was recently analysed at the seismic stations located in the Mozambique channels (Barruol et al 2016) and the map of this swell propagation in the SW Indian Ocean was presented in their Fig. 3.…”
Section: Austral Swell-related Seismic Noise Recorded By a Seismologimentioning
confidence: 95%
“…It has been shown that cyclones in the SW Indian Ocean region generate large microseismic noise in both the PM and the SM frequency band. PM sources are generated in coastal areas by direct interaction of the swell with the sloping sea floor, such as shown by the example of the cyclone Felleng (January 2013) hitting the island of Tromelin located 600 km NNW of La Réunion (Barruol et al 2016). SM sources are dominantly generated in the deep ocean by standing waves developing mainly in the neighbourhood of storm areas occurring at high latitudes (Stutzmann et al 2009;Ardhuin et al 2012), but also in low latitude areas and associated to tropical storms such as demonstrated for cyclone Dumile that occurred in early January 2013 (Davy et al 2014).…”
Section: Yc L O N I C S W E L L a N A Ly S E S At L A Ré U N I O N mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a new method of observing swells emerged, based on seismic records of typhoon-generated noise (i.e., "microseisms") [15][16][17][18][19][20]. Seismic noise is used here as a proxy for swell monitoring in areas where ocean wave gauges are poorly instrumented.…”
Section: Introductionmentioning
confidence: 99%
“…A mangrove formation ranging from shrub to forest stands grows in the salt waters of the back and windward edge of the lagoon (Lambs et al, 2016). Europa is characterized by a high-energy environment under the influence of south to southeasterly trade winds (strongest in austral winter) and occasionally impacted by tropical cyclones in austral summer (Barruol et al, 2016). A train of anticyclonic ocean eddies traveling through the Mozambique Channel transports tropical water southward, eventually feeding the Agulhas Current (Beal et al, 2011).…”
mentioning
confidence: 99%